Elthusa arnoglossi sp. nov. (Crustacea: Isopoda: Cymothoidae), a branchial parasite of flatfishes (Bothidae) from the Chesterfield Islands, New Caledonia - Trilles, Jean-Paul; Justine, Jean-Lou (Zootaxa, 2006)
The cymothoid isopod Elthusa arnoglossi sp. nov., a branchial parasite of Arnoglossus sp. (Teleostei, Bothidae) from the Chesterfield Islands, New Caledonia (southwestern Pacific), is described and figured. The new species is characterised by the asymmetric body of the female, always twisted to the right side, antenna composed of 18 articles in both sexes, all female pereopods with a distinctly dilated merus and uropods almost reaching posterior margin of pleotelson in both sexes; males have the body with pereonites 1–3 distinctly wider than pereonites 4–5 and a well developed appendix masculina. Within the genus the species is similar only to E. samariscii (Shiino, 1951), a parasite of Samaris cristatus (Teleostei, Samaridae) from the Indo-Pacific. E. arnoglossi is the first Elthusa reported on fish from the genus Arnoglossus.